Building Students Vocabulary To Support Their Basic Writing Skills Through Picture Series - Menawan*, Alvian; Binawan, Heribertus (Universitas Syiah Kuala, 2023)
This study aims to determine whether the use of picture series media to build students' vocabulary to supports their basic writing skills. This study used the pre-experimental method with one group pretest posttest design and data collection was carried out by administering pretest, treatment and posttest. The sample of this research was students of class VIII A of SMP N 1 Sedayu, which consisted of 30 students in the 2023/2024 academic year. The research sample was chosen randomly. The findings of the researchers show that the mean score of students in basic writing skill as evidenced by the post-test was 13.50% higher than the students mean score in the pre-test of 76.76 and the value of the t-test was greater than the table- t (t-testt-table). Basic writing score was bigger than t-table (Sig.0.05 = 0.0010.05), meaning that the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. In other words, the use of pictures series can build students' vocabulary mastery effectively to help their basic writing skills.